2011
DOI: 10.1089/apc.2010.0254
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of the Potential Utility of Computational Modeling as an HIV Treatment Selection Tool by Physicians with Considerable HIV Experience

Abstract: The HIV Resistance Response Database Initiative (RDI), which comprises a small research team in the United Kingdom and collaborating clinical centers in more than 15 countries, has used antiretroviral treatment and response data from thousands of patients around the world to develop computational models that are highly predictive of virologic response. The potential utility of such models as a tool for assisting treatment selection was assessed in two clinical pilot studies: a prospective study in Canada and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 15 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…By assessing a whole suite of candidate therapies at a time, such a system can rank these with respect to their estimated probability of success and suggest highly promising drug combinations. The first such system that became generally available was THEO (Therapy Optimization) from the geno2pheno suite [15,16], followed by the EuResist interpretation engine [17] and, more recently, by an offer from the HIV Resistance Response Database Initiative [18]. …”
Section: Estimation Of Therapy Effectivenessmentioning
confidence: 99%
“…By assessing a whole suite of candidate therapies at a time, such a system can rank these with respect to their estimated probability of success and suggest highly promising drug combinations. The first such system that became generally available was THEO (Therapy Optimization) from the geno2pheno suite [15,16], followed by the EuResist interpretation engine [17] and, more recently, by an offer from the HIV Resistance Response Database Initiative [18]. …”
Section: Estimation Of Therapy Effectivenessmentioning
confidence: 99%
“…The application of the models as a treatment decision-making aid has been assessed in prospective clinical pilot studies involving highly experienced HIV physicians in well-resourced settings and found to be a useful clinical tool. 9 The RDI models are made freely available as a treatment-support tool, the HIV Treatment Response Prediction System (HIV-TRePS), via http://www.hivrdi.org .…”
Section: Introductionmentioning
confidence: 99%
“…The models have been used to power a free experimental web-based HIV treatment response prediction system (HIV-TRePS) assessed by experienced HIV physicians in two clinical pilot studies as a useful aid to clinical practice [12]. …”
Section: Introductionmentioning
confidence: 99%